Influence of mineral and organic nitrogen on symbiotic fixation of nitrogen by soybeans - Ruschel, Alaides Puppin; Ruschel, Renato; Almeida, Dejair Lopes de; Suhet, Allert Rosa (Pesquisa Agropecuaria Brasileira, 2014)
In a greenhouse experiment the effects of Rhizobium inoculation and nitrogen fertilization (sodium nitrate, amonium sulphate, amonium nitrate, and urea) were studied for two soybean varieties (IAC 70-25 and Mineira). Nodulation, nitrogenase activity by acetylene reduction, amount of nitrogen in plants, and weight of plants were observed. The inoculated plants grown in soil free of nitrogen added did not develop too much, and were comparable in weight with the ones not inoculated; however, they presented the greatest number and weight of nodules, and nitrogenase activity when the mass of nodules was taken in account. Among treatments which received different sources of nitrogen, the nodulation was heavier in presence of urea and consequently the nitrogenase activity was bigger in that particular treatment. Plants from amonium nitrate and urea treatments presented higher, however not significant, etilene evolution and total nitrogen in plants, suggesting a sinergetic effect between the nitrogen taken from the soil and the nitrogen fixed from the atmosphere by the Rhizobium.